Stima della portata della fistola artero-venosa mediante termodiluizione nei pazienti in emodialisi cronica: esperienza monocentrica. - Enrico Varricchio; Alessandro Puntoni; Domenico Giannese; Claudia Mannucci; Piera Serio; Raffaele Caprioli; Alberto Lippi; Maria Francesca Egidi; Adamasco Cupisti (AboutScience Srl, 2020)
Purpose: Vascular access surveillance in hemodialysis is today an important challenge for nephrologist.  Low blood flow is a risk factor for development of thrombosis of native fistula or graft. The aim of the study is to evaluate the correspondence between flow measurement by thermodilution and Color Doppler, and to identify flow rate values using the Blood temperature monitor (BTM) method in the case of stenosis. Methods: We evaluated 29 patients on chronic hemodialysis. The evaluation of blood flow with BTM were performed during the first hour of the hemodialysis session. All patients underwent a color doppler of vascular access within 10 days from the BTM measurements. Results: The mean vascular access flow calculated with BTM resulted 1142 ± 700 ml/min and there was a correlation with color doppler data 1199 ± 644 ml/min (p=0,0001 r=0,829). The flow of patients with hemodynamically significant stenosis was 332 ± 92 ml/min with a minimum value of 270 ml/min and a maximum value of 440 ml/min. Conclusion: the correspondence between thermodilution and color doppler support the implementation of intradialitic evaluation of the vascular access blood flow with the BTM method. Thermodilution allows to identify earlier patients with high risk of vascular access failure and the need for further diagnostic and therapeutic investigations.